REAL ECONOMIC CONVERGENCE IN THE EUROPEAN UNION - Ștefan Bulboacă (Journal of Smart Economic Growth, 2023)
This paper evaluates real economic convergence (REC) for countries and regions within the European Union. The research aims to gather information about the socioeconomic evolution and development of the EU members and decide if the convergence was successful. Real economic convergence within the EU will be descriptively analysed at the national and regional levels using the real GDP and the GDP/Capita indicators. For a better understanding, the analysis considers the indicator poverty risk and social exclusion, and the two types of convergence will be examined comparatively. The research includes geopolitical maps of the European Union to compare the nations and regions at specific points in time, and the data used for the maps will be used to observe a graph representation of their evolution during the regarded timeframe. The graph evolution will be calculated with a simple regression line to mathematically ascertain the effectiveness of the regression.